1991
DOI: 10.1104/pp.97.2.509
|View full text |Cite
|
Sign up to set email alerts
|

Culm Brittleness of Barley (Hordeum vulgare L.) Mutants Is Caused by Smaller Number of Cellulose Molecules in Cell Wall

Abstract: The physicochemical nature of the cell wall was determined in the fourth internode of three isogenic brittle mutants of barley (Hordeum vulgare L.) and corresponding nonbrittle strains. Cellulose contents of the brittle culms were 17.5 to 20.3% of those of corresponding nonbrittle strains. No major difference was found in lignin and noncellulose components (except glucose) between brittle and nonbnttle strains. Maximum bending stresses of brittle culms were 38.0 to 54.2% of those of corresponding nonbrittle st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1
1

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 19 publications
4
57
1
1
Order By: Relevance
“…In the brittle culm mutants of barley, there is a correlation between cellulose content and the maximum load at yield (Kokubo et al, 1989(Kokubo et al, , 1991, and it is similar to that observed in this study. The irx mutations appear to affect the bending modulus more dramatically than the maximum load at yield.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In the brittle culm mutants of barley, there is a correlation between cellulose content and the maximum load at yield (Kokubo et al, 1989(Kokubo et al, , 1991, and it is similar to that observed in this study. The irx mutations appear to affect the bending modulus more dramatically than the maximum load at yield.…”
Section: Discussionsupporting
confidence: 79%
“…The physical properties of the stem, which reflect the properties of the cell wall (Kokubo et al, 1989(Kokubo et al, , 1991; are radically altered. The stem material of irx plants is both weaker and much less stiff than that of the wild type (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze-fracture studies of the plasma membrane have shown unique "rosette" structures associated with the ends of microfibrils, suggesting that these rosettes are the site of cellulose synthesis (reviewed in Brown, 1996). Confirmation of these results has come from Arabidopsis ( rsw1 ) and barley (brittle culm) mutants that have less cellulose than their respective wild types (Kokubo et al, 1991;Arioli et al, 1998a). Plasma membranes from the cells affected in these mutants exhibit greatly decreased numbers of rosettes.…”
Section: Introductionmentioning
confidence: 52%
“…Cellulose content has been correlated with brittleness in barley internodes. Brittle mutants contained onefifth normal levels of cellulose (Kokubo et al 1989(Kokubo et al , 1991. Bailey (1964) showed that higher weight gains are associated in ryegrass with lower cellulose content which is related to tensile strength.…”
Section: Anatomy and Morphologymentioning
confidence: 99%